Ethiologic diagnosis of dementia syndrome. - Erélido Hernández Valero; María Octavina Rodríguez Roque (Medisur)
Dementia prevalence is between 4,5 and 18,5%, the inferior numbers are in the underdeveloped countries. Studies carried out in Cuba, shows approximately a 10% for more than 60 year old persons, what makes consider dementia as a health problem of huge importance. That is why the existence of a practical guide for its etiological diagnosis is of supreme necessity. This study engulfs diverse criteria to reach the diagnosis of dementia syndrome, as well as the diseases that may cause it, foretell it or accelerate it. Numbers are presented, and a series of valuations about dementia, the slight cognitive aggravation, Alzheimer disease, vascular dementia, dementia by Lewy bodies, and front temporal dementia, as well as other kinds of dementia.